Determinants of self-rated health of Francophone seniors in a minority situation in Canada - Alimezelli, Hubert Tote; Leis, Anne; Karunanayake, Chandima; Denis, Wilfrid (Linguistic Minorites and Society, 2013)
Résumé La tendance actuelle montre que les institutions des services de santé et les gouvernements répondent de façon inadéquate aux besoins de plus en plus nombreux d’accès aux services de santé par les populations vieillissantes du Canada et d’autres pays développés. Après l’analyse de l’enquête post-censitaire 2006 de Statistiques Canada sur la Vitalité des Minorités de Langue Officielle, cette étude démontre qu’outre l’age, et en plus d’autres déterminants, les barrières linguistiques auxquelles font face les aînés de langue officielle en situation minoritaire affectent davantage l’autoévaluation de leur santé. Cette étude suggère quelques pistes de solution dont la compréhension des réalités contextuelles, l’amélioration de l’environnement linguistique et des services de santé dans la langue minoritaire. Mots-clés : déterminants de la santé, statut minoritaire, santé perçue, minorités linguistiques, aînés Abstract Current trends show that governments and health institutions in Canada and other developed nations are responding inadequately to the growing need for health services of the increasingly aging population. The Analysis of Statistics Canada’s 2006 post-census Survey on the Vitality of Official Language Minorities show that in addition to age and other socio-demographic determinants, linguistic barriers affect the self-rated health of seniors of official languages living in a minority situation. This study suggests among other things a greater understanding of Official language minorities’ contextual realities, the improvement of both the linguistic environment and services in the minority language. Keywords: health determinants, minority status, self-rated health, linguistic minorities, older adults

Santé mentale des jeunes des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : l’état des lieux - Beaton, Ann M.; Benoit, Monique; Mulatris, Paulin; Dupuis, Jérémie B. (/Youth Mental Health in Official Language Minority Communities (OLMCs) in Canada: Situation Analysis Minorités linguistiques et société, 2018)

Santé mentale et maladies mentales des jeunes francophones de 15 à 24 ans : données de l’Enquête sur la santé dans les collectivités canadiennes – Santé mentale 2012 - Bouchard, Louise; Batista, Ricardo; Colman, Ian (Minorités linguistiques et société, 2018)
a plupart des maladies mentales apparaissent à l’adolescence ou au début de la vie adulte ; elles influent sur les réussites scolaires, les possibilités et les succès professionnels ainsi que les relations personnelles et peuvent avoir des répercussions tout au long de la vie. Bien que la majorité des jeunes traversent leur adolescence sans problèmes, une proportion suffisamment importante montre toutefois un profil préoccupant dont il faut prendre acte. L’objectif de cet article est de brosser, à partir des données de l’Enquête sur la santé dans les collectivités canadiennes – Santé mentale (ESCC-SM 2012), un portrait de la santé mentale des jeunes francophones de 15 à 24 ans vivant en situation linguistique minoritaire et de le comparer à celui des jeunes francophones vivant au Québec. Mots-clés : identité ethnolinguistique, continuité culturelle, minorité francophone, jeunes adultes, santé mentale

Les minorités linguistiques du Canada et la santé - Bouchard, Louise; Desmeules, Martin (Politiques de santé, 2013)
Résumé Les minorités de langue officielle (les francophones hors-Québec et les anglophones du Québec) représentent près de 6,4 % de la population canadienne. Bien que le français et l’anglais aient un statut d’égalité juridique selon la Constitution canadienne, il y a lieu de s’interroger sur leur égalité dans le domaine de la santé : les communautés francophones et anglophones du Canada, selon leur statut de minorité ou de majorité, présentent-elles le même profil santé ? Ont-elles accès aux mêmes services de santé et dans les mêmes conditions ? L’objectif de cet article cet article est de rendre compte des enjeux de santé reliés au fait d’appartenir à une minorité linguistique. Nos recherches permettent de mettre en évidence des disparités sociales et de santé qui peuvent être attribuées au fait minoritaire. Dans le contexte canadien des deux langues officielles, une politique de santé équitable devra dorénavant pren dre en considération la situation linguistique minoritaire comme déterminant de la santé. Abstract Official language minorities (Francophones outside of Quebec and Anglophones in Quebec) make up about 6.4% of the Canadian population. Even though the Canadian constitution gives legal equality status to French and English, there is still room to ask if this equality is maintained in the health sector. In other words, do Francophone and Anglophone communities of Canada have the same health profiles regardless of their minority or majority status? Do they have access to the same health services and in the same conditions? The objective of this paper is to identify the health issues associated with belonging to a linguistic minority. Our research allows us to highlight the social and health disparities that can be attributed to belonging to a minority. In the Canadian context, which has two official languages, an equitable health policy will have to take into consideration language as a determinant of health.

Minorités de langue officielle du Canada : égales devant la santé ? - Bouchard, Louise; Desmeules, Martin (Presses de l’Université du Québec, 2011)

La santé mentale des francophones et des anglophones vivant en situation minoritaire au Canada [infographie] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Mental health status of Francophones and Anglophones living in minority situations in Canada [infographic] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Profil santé mentale des communautés francophones en situation minoritaire au Canada. Rapport abrégé - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa; Colman, Ian (Université d'Ottawa et Institut du Savoir Montfort, 2019)

Acculturation, vitality, and bilingual healthcare - Bourhis, Richard Y.; Montreuil, Annie (The Oxford handbook of acculturation and health, 2017)
Chapter: 4

Impact des barrières linguistiques sur la sécurité des patients et la qualité des soins. Rapport final - Bowen, Sarah (Société Santé en français, 2015)

The impact of language barriers on patient safety and quality of care. Final report - Bowen, Sarah (Société Santé en français, 2015)

Dans la langue officielle de son choix : la loi canadienne sur les langues officielles et la notion de « choix » en matière de services publics - Charbonneau, François (Lien social et Politiques, 2011)
L’article s’intéresse à la notion de choix en matière de services publics à la lumière de l’expérience de la notion de « langue de son choix » incluse dans les diverses législations canadiennes depuis plus de quarante ans, c’est-à-dire depuis l’adoption de la Loi sur les langues officielles au Canada. Cet exemple montre bien comment le choix en matière de services publics peut avoir des conséquences délétères non intentionnelles pour les populations les plus vulnérables, dans ce cas-ci, les francophones vivant en situation minoritaire.

La pénurie de professeures de sciences infirmières au Canada et ses effets sur les programmes de formation en sciences infirmières offerts en français - Chartrand, Julie; Vandyk, Amanda; Beké, Émilie; Balasa, Rebecca; Loranger, Catherine; Muray, Mwali; Chartrand, Mariève; Baker, Cynthia (Minorités linguistiques et société, 2019)
Cette étude qualitative décrit la pénurie de professeures en sciences infirmières et ses effets actuels et potentiels sur les programmes canadiens de formation en sciences infirmières offerts en français, ainsi que les stratégies préconisées par les directrices de ces programmes afin d’en atténuer les effets. Les effets de la pénurie sont particulièrement préoccupants dans le cas des programmes offerts dans un contexte francophone minoritaire ou en région éloignée. La pénurie mettrait en péril les programmes offerts en français et menacerait, par le fait même, la qualité des services de santé offerts aux communautés francophones minoritaires au Canada. Mots-clés : pénurie professorale, sciences infirmières, professionnels de la santé, services et soins de santé en français, communautés francophones en situation minoritaire

Multilingualism (but not always bilingualism) delays the onset of Alzheimer disease: Evidence from a bilingual community - Chertkow, Howard; Whitehead, Victor; Phillips, Natalie; Wolfson, Christina; Atherton, Julie; Bergman, Howard (Alzheimer Disease and Associated Disorders, 2010)
A recent paper by Bialystok et al in Neuropsychologia (vol. 45, pgs. 459 to 464) suggested that early bilingualism produced a statistically significant 4.1-year delay in onset of memory loss symptoms in older individuals with Alzheimer disease, possibly reflecting an increase in the cognitive reserve of these individuals. That study focused on multilingual elderly patients of whom 90% were immigrants. Our memory clinic, in Montreal Canada, has the advantage of having a large set of individuals who are either multilingual immigrants to Canada, or who are nonimmigrants but raised in both official languages of Canada—French and English. We thus attempted to replicate the above findings using a larger cohort in a different setting. We examined age at diagnosis of Alzheimer disease and age at symptom onset for all unilingual versus multilingual participants, and then for those who were nonimmigrant English/French bilinguals. Overall, we found a small but significant protective effect of more than 2 languages spoken, but we found no significant benefit in bilinguals overall in relation to age at diagnosis or age at symptom onset. However, in the immigrant group, the results mirrored those of Bialystok et al with 2 or more languages delaying the diagnosis of Alzheimer disease by almost 5 years. A trend toward the same effect was also seen in nonimmigrants whose first language was French. In contrast, in nonimmigrants whose first language was English, no such effect was found. These results are discussed in relation to the earlier findings and the theory of cognitive reserve.

Quel avenir pour le projet autonomiste des communautés francophones en situation minoritaire ? Réflexion sur les politiques publiques canadiennes en matière de langues officielles - Chouinard, Stéphanie (Minorités linguistiques et société, 2012)
Nous tentons de mettre au jour quelques possibilités d’application, en matière de politiques publiques, des revendications de reconnaissance politique des communautés francophones en situation minoritaire (CFSM) du Canada, que nous organisons selon deux optiques différentes, soit l’autonomie et l’intégration. Après quelques considérations d’ordre sociopolitique et juridique, nous plaiderons pour une asymétrie dans l’élaboration des politiques publiques relatives à ces communautés. Nous soulignerons aussi le poids des enjeux de pouvoir dans la relation entre l’État et les CFSM, notamment sur le plan de la gouvernance, dans l’élaboration de ces politiques. Mots-clés : autonomie, politiques publiques, communautés francophones en situation minoritaire, communautés de langue officielle au Canada, participation politique

Bien vieillir dans sa langue, sa culture et sa communauté. Soutien d’institutions fédérales clés et portrait des aînés anglophones du Québec - Commissariat aux langues officielles (Gouvernement du Canada, 2013)

L’offre active une culture de respect, une culture d’excellence : dépliant [infographie] - Commissariat aux langues officielles (2019)
fs-ref-orig: Commissariat aux langues officielles. (2019). L’offre active une culture de respect, une culture d’excellence : dépliant [infographie]. fs-code-orig: Commissariat aux langues officielles-2019

L’offre active une culture de respect, une culture d’excellence : guide complet [infographie] - Commissariat aux langues officielles (2017)
fs-ref-orig: Commissariat aux langues officielles. (2017). L’offre active une culture de respect, une culture d’excellence : guide complet. fs-code-orig: Commissariat aux langues officielles-2017.

Ma santé, ta santé, notre santé. Étude sur la santé mentale et les comportements à risque des jeunes adultes dans cinq universités au coeur du Canada - de Moissac, Danielle; Gueye, Ndeye Rokhaya; Rocque, Rhéa (Consortium national de formation en santé, Université de Saint-Boniface, 2019)
La transition de l’adolescence à la vie adulte constitue une des plus importantes transitions de la vie. À ce stade, le jeune doit développer des habiletés pour être en mesure de se prendre en charge et gérer ses responsabilités académiques et financières tout en maintenant un mode de vie sain. Des études démontrent que des perturbations à ce stade de vie peuvent avoir des conséquences importantes sur la santé psychologique et l’adaptation au changement, et qu’une instabilité émotionnelle peut avoir des retombées sur la performance et le fonctionnement psychosocial. Le milieu universitaire occupe une place privilégiée en tant que lieu d’intervention pour la promotion de la santé pour ces jeunes en raison du contact direct avec les étudiants au cours de plusieurs années. Une stratégie en matière de santé mentale, développée par la Commission de la santé mentale du Canada, souligne que les efforts de promotion en santé mentale et de prévention des troubles mentaux seront plus efficaces si les axes suivants sont respectés 1) savoir à qui s’adresser; 2) renforcer les éléments de protection et réduire les facteurs de risque; 3) fixer des buts clairs; 4) donner aux collectivités ce dont elles ont besoin pour agir; et 5) planifier pour le long terme. Ce projet de recherche s’inspire de cette stratégie : notre but à long terme est de favoriser le bien-être des jeunes adultes qui fréquentent un établissement universitaire en développant un outil de dépistage et des initiatives d’appui soutenables sur le campus et dans la communauté, selon les ressources disponibles. Pour ce faire, nous devons d’abord prendre connaissance de l’état de santé mentale de la population étudiante et des facteurs de risques et de protection qui leur sont propres. Ainsi, les efforts de prévention seront plus efficaces puisqu’ils seront conçus en fonction des besoins de la population cible et en consultation avec cette dernière. Cette étude a été menée dans cinq universités dans trois provinces, soit le Manitoba, l’Ontario et le Québec, dans le but de mieux comprendre l’effet du contexte linguistique sur la santé mentale et les comportements à risque des jeunes universitaires. Les cinq établissements choisis sont principalement des petites universités en contexte linguistique majoritaire (Brandon University et Université du Québec en Abitibi-Témiscamingue) ou minoritaire (Université de Saint-Boniface et Université Bishop’s). De plus, des participants de l’unique université bilingue du pays (Université d’Ottawa) ont participé. Ainsi, nous serons en mesure d’analyser les données en fonction de divers facteurs déterminants, dont le milieu linguistique dans lequel évolue l’étudiant. L’objectif principal de l’étude est de prendre connaissance de l’état de santé mentale et des comportements à risque prédominants des jeunes universitaires en contextes linguistiques majoritaires et minoritaires au Canada et d’identifier les facteurs de protection et de risque associés à leur bien-être. Notre but ultime est d’appuyer les étudiants, particulièrement ceux dans le besoin, dans leur atteinte d’une réussite académique. Ce rapport est descriptif : il présente les données générales se rapportant aux profils sociodémographique et ethnolinguistique, à l’état de santé mentale et aux comportements associés à cet état, ainsi qu’à la sécurité routière, au taxage et au harcèlement sexuel, aux pratiques sexuelles, à la consommation d’alcool, de drogues et de tabac, et à l’usage des nouvelles technologies; le tout, selon le genre et pour chacun des établissements d’enseignement postsecondaire. Un sondage a été distribué, sur papier ou en ligne, en fin novembre 2018 et en février 2019; au total, 2075 étudiants ont participé. Des analyses statistiques de fréquences et de proportions, selon le genre, ont été utilisées pour décrire les participants et leurs comportements.
fs-ref-orig: de Moissac, D., Gueye, N. R. et Rocque, R. (2019). Ma santé, ta santé, notre santé. Étude sur la santé mentale et les comportements à risque des jeunes adultes dans cinq universités au coeur du Canada. Consortium national de formation en santé, Université de Saint-Boniface et Université du Québec en Abitibi-Témiscamingue. fs-code-orig: de Moissac-2019b

My Health, your health, our health. A study on mental health and risk-taking behaviors of young adults on five university campuses in the heart of Canada - de Moissac, Danielle; Gueye, Ndeye Rokhaya; Rocque, Rhéa (Consortium national de formation en santé, Université de Saint-Boniface, 2019)
The transition from adolescence to adulthood is a time of dramatic change in one’s life. At this stage, youth are developing skills to be able to support themselves and manage academic and financial responsibilities, while maintaining a healthy lifestyle. Studies have shown that disturbances at this stage may have a strong impact on one’s psychological health and ability to adapt to change; emotional instability may have repercussions on performance and psychosocial functioning. Due to direct contact with young adults, postsecondary institutions are priviledged settings for health promotion activities. A mental health strategy developed by the Mental Health Commission of Canada suggests that to successfully promote health, and treat and prevent mental health issues, the following should be considered: 1) know who to reach; 2) strengthen protective factors and reduce risk factors; 3) set clear goals; 4) give communities what they need to take action; and 5) plan for the long term. This research project builds on this strategy. Our long term goal is to promote the well-being of university students by developing a screening tool and developing sustainable initiatives on campus and within the community, taking into consideration available resources. As such, we must first gain insight into the mental health status of the student population, including the risk and protective factors specific to these students. Thus, health promotion efforts will be more efficient, as they will have been created according to student needs and in consultation with this population. This study was conducted in five universities in three provinces, Manitoba, Ontario and Quebec, to gain insight into the impact of the linguistic context on mental health and risk-taking behaviors of students. The five participating universities were chosen mainly because of their small size and linguistic environment: Brandon University and the Université du Québec en Abitibi-Témiscamingue are in linguistic majority settings, whereas the Université de Saint-Boniface and Bishop’s University are in linguistic minority communities. In addition, participants were recruited from the only bilingual university in the country (University of Ottawa). Thus, data will be analysed according to various influencing factors, including the linguistic environment. The main objective of this study is to gain insight into the mental health status and predominant risk behaviors of university students in both majority and minority linguistic settings in Canada and to identify protective and risk factors relative to their well-being. The ultimate goal is to help those in need achieve academic success. This report is descriptive: it presents general data related to sociodemographic and ethnolinguistic profiles, mental health and related behaviors, road safety, bullying and sexual harassment, sexual practices, alcohol, drug and tobacco use and use of new technologies, according to gender, for each of the postsecondary institutions. A survey was conducted online or in print form at the end of November 2018 and in February 2019. In total, 2075 students participated. Statistical analysis of frequencies and proportions according to gender were used to describe participants and their behaviors
fs-ref-orig: de Moissac, D., Gueye, N. R., & Rocque, R. (2019). My Health, your health, our health. A study on mental health and risk-taking behaviors of young adults on five university campuses in the heart of Canada. Consortium national de formation en santé, Université de Saint-Boniface et Université du Québec en Abitibi-Témiscamingue. fs-code-orig: de Moissac-2019c

Accessibility and active offer: Health care and social services in linguistic minority communities - Drolet, Marie; Bouchard, Pier; Savard, Jacinthe (University of Ottawa Press, 2017)
This edited volume examines language issues within the active offer of health and social services in francophone and anglophone minority communities. Action based, it will help shape the leaders of tomorrow. It is imperative that we train leaders who are able to intervene efficiently with service users and to support a better organization of the workplace. It is especially important to look at the many issues related to postsecondary training and human resources, such as recruiting and keeping these leading professionals. Accessibility and Active Offer thus combines theory and empirical data to help future professionals understand the workplace issues of accessibility and active offer of minority-language services. This English-language adaptation of Accessibilité et offre active features an additional chapter by Richard Bourhis on issues specific to Anglophone communities in Québec.

L'intervention du gouvernement fédéral canadien en matière de droits linguistiques dans le secteur de la santé - Farley, Roger; Guillemette, Roger; Rivest, François (2015)

Profil statistique 2016 des personnes âgées francophones au Canada : faits saillants [infographie] - Fédération des aînées et aînés francophones du Canada (2019)
fs-ref-orig: Fédération des aînées et aînés francophones du Canada. (2019). Profil statistique 2016 des personnes âgées francophones au Canada : faits saillants [infographie]. fs-code-orig: Fédération des aînées et aînés francophones du Canada-2019b

Profil statistique 2016 des personnes âgées francophones au Canada [Rapport] - Fédération des aînées et aînés francophones du Canada (2019)
fs-ref-orig: Fédération des aînées et aînés francophones du Canada. (2019). Profil statistique 2016 des personnes âgées francophones au Canada [Rapport]. fs-code-orig: Fédération des aînées et aînés francophones du Canada-2019a

La gouvernance des communautés francophones en situation minoritaire et le partenariat avec l’État - Forgues, Éric (Politique et Sociétés, 2010)
Nous abordons ici des enjeux que pose le partenariat entre les organismes communautaires francophones en situation minoritaire (CFSM) et l’État fédéral canadien. S’il semble répondre aux aspirations des communautés concernant la prise en charge de leur développement, en favorisant notamment une démarche fondée sur le principe de la gouvernance partagée, ce partenariat comporte malgré tout des exigences administratives qui paraissent tempérer l’autonomie et la libre gouvernance des CFSM. La participation des organismes francophones à l’élaboration et à la mise en oeuvre des politiques publiques s’accompagne d’une bureaucratisation de leurs activités communautaires et d’une réévaluation de leurs structures de représentation. Tenus de représenter plus formellement l’intérêt général de la communauté et de collaborer directement avec l’État pour lui permettre d’atteindre ses objectifs, ils sont poussés à une action qui se heurte, constate-t-on, à de nouveaux impératifs de légitimité. Ces derniers ont pour effet de remettre en question l’arrangement corporatiste qui s’est établi entre eux et l’État. C’est cet enjeu de légitimité qui pèse sur le nouveau mode de gouvernance des CFSM que nous avons voulu porter au jour dans notre recherche, dont nous présentons quelques éléments dans le présent article.

Prévalence de la dépression majeure chez les arthritiques des populations canadiennes : étude comparative entre anglophones majoritaires et francophones en situation linguistique minoritaire - Fotsing, Salomon; Nzokem, Aubain H.; Grenier, Jean; Imbeault, Pascal; Batal, Malek; Bouchard, Louise; Chomienne, Marie-Hélène (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectif La santé mentale et l’arthrite sont deux maladies reconnues comme étant des enjeux majeurs en santé publique. La situation minoritaire des francophones est reconnue comme un déterminant de la santé. L’objectif de cette étude est de déterminer la prévalence de la dépression majeure chez les arthritiques adultes des populations francophones minoritaires comparativement à la majorité anglophone. Méthode Analyse secondaire de l’ESCC (fusion de 2003 (cycle 2.1), 2005 (cycle 3.1), 2007 (cycle 4.1), 2008 et 2009) excluant le Québec. La variable langue a été construite selon un algorithme pré-existant réunissant la langue maternelle, de conversation, d’entrevue et de préférence. La dépression majeure était définie selon les critères du DSM IV. La présence ou non d’arthrite était une variable auto-rapportée. Les prévalences et rapports de cotes pour la dépression dans la population arthritique ont été calculés et ajustés en fonction de divers facteurs (socioéconomiques, isolement social, accès aux services de santé). Résultats L’étude identifiait 159 426 anglophones et 10 658 francophones. Parmi les sujets avec arthrite (27 %), la prévalence de la dépression était de 8,5 % et de 8,4 % chez les francophones et les anglophones, respectivement; chez les hommes, les anglophones étaient plus à risque de faire une dépression que les francophones: OR=2,36 (IC 95%: 2,07-2,70) c. OR=1,87 (IC 95%: 1,20-2,91). Cette tendance ne se retrouvait pas chez les femmes. Conclusion Notre échantillon démontre que dans une population arthritique, la dépression semble toucher plus particulièrement les hommes anglophones. Cependant il faut souligner la petite taille de l’échantillon.

Access to health care services and self-perceived health of canada's official-language minorities [master's thesis, University of Ottawa] - Gagnon-Arpin, Isabelle (University of Ottawa, 2011)
fs-ref-orig: Gagnon-Arpin, I. (2011). Access to health care services and self-perceived health of canada's official-language minorities [master's thesis, University of Ottawa]. uO Research. http://dx.doi.org/10.20381/ruor-4657 fs-code-orig: Gagnon-Arpin-2011c

Accès et utilisation des services de santé en langue minoritaire - Gagnon-Arpin, Isabelle; Bouchard, Louise; Leis, Anne; Bélanger, Mathieu (La vie dans une langue officielle minoritaire au Canada, 2014)
fs-ref-orig: Gagnon-Arpin, I., Bouchard, L., Leis, A. et Bélanger, M. (2014). Accès et utilisation des services de santé en langue minoritaire. Dans R. Landry (dir.), La vie dans une langue officielle minoritaire au Canada (p. 195-221). Presses de l’Université Laval. fs-code-orig: Gagnon-Arpin-2014b

Access and use of health care services in the minority language - Gagnon-Arpin, Isabelle; Bouchard, Louise; Leis, Anne; Bélanger, Mathieu (Life within an official language minority in Canada, 2014)
fs-ref-orig: Gagnon-Arpin, I., Bouchard, L., Leis, A., & Bélanger, M. (2014). Access and use of health care services in the minority language. In R. Landry (Ed.), Life within an official language minority in Canada (pp. 177-198). Canadian institute for research on Linguistic Minorities. fs-code-orig: Gagnon-Arpin-2014a

Investir dans notre avenir 2018-2023. Plan d'action pour les langues officielles - Gouvernement du Canada (Plan d'action pour les langues officielles, 2018)
fs-ref-orig: Gouvernement du Canada. (2018). Investir dans notre avenir 2018-2023. Plan d'action pour les langues officielles. fs-code-orig: Gouvernement du Canada-2018a

Investing in our future 2018-2023. Action plan for official languages - Government of Canada (Action plan for official languages, 2018)
fs-ref-orig: Government of Canada. (2018). Investing in our future 2018-2023. Action plan for official languages. fs-code-orig: Government of Canada-2018b

Portrait des services bilingues offerts au sein des hôpitaux canadiens. Rapport - Guignard Noël, Josée; LeBlanc, J.; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2016)

Étude de référence sur les services bilingues au sein des établissements de santé canadiens - Guignard Noël, Josée; LeBlanc, Joannie; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2016)

Client and family information sheet: Access to health and social services in Official Languages Standard - Health Standards Organization (2018)
The CAN/HSO 11012:2018 Access to Health and Social Services in Official Languages Standard provides guidelines of excellence to help organizations aim to improve access to health and social services across the continuum of care in Canada’s two official languages – French and English. This information sheet explains what should be expected from health and social service organizations applying this standard.

Accès aux services de santé et aux services sociaux dans les langues officielles - Health Standards Organization / Organisation de normes en santé (2018)
La norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais.
Ce document qui décrit la norme créé en 2018 n'est plus disponible. La norme a été révisée en 2022 et c'est cette révision de 2022 qui peut être acheté sur la page web suivante: https://healthstandards.org/fr/standard/acces-aux-services-de-sante-et-aux-services-sociaux-dans-les-langues-officielles-confirmation/

Feuillet d'information pour les usagers et les familles : norme sur l'Accès aux services de santé et aux services sociaux dans les langues officielles - Health Standards Organization / Organisation de normes en santé (2018)
La norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais. Ce feuillet d'information explique ce à quoi les usagers peuvent s'attendre des organismes de santé et de services sociaux qui appliquent cette norme.

Physical inactivity among Francophones and Anglophones in Canada - Imbeault, Pascal; Makvandi, Ewa; Batal, Malek; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective Leisure-time physical activity participation is influenced by various socio-demographic factors. Recent evidence suggests that being part of a minority negatively impacts an individual’s health status. The objective of this study was to compare inactive leisure-time physical activity between the Francophone minority and the Anglophone majority in Canada. Methods Data from the fusion of cycles 2.1, 3.1, 4.1, 2008 and 2009 of the Canadian Community Health Survey (CCHS) were used. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. Leisure-time physical activity was based on a questionnaire provided during the interview. Factors associated with inactive leisure time were examined using logistic regression models. Results Francophones were more likely than Anglophones to be physically inactive in their leisure time (49.1% vs. 47.2%). A greater percentage of Francophones had poor self-perceived health, were older, were single, had lower education, had higher rate of unemployment and lived in rural areas compared to Anglophones. When these socio-demographic factors were taken into account, there were no further differences in the likelihood of being inactive between Francophones and Anglophones. Conclusion The Francophone minority in Canada is characterized by socio-demographic factors that have a negative impact on leisure-time physical activity participation.

Sources de données de Statistique Canada sur les minorités de langue officielle (n°91-549 -X) - Lafrenière, Sylvie (Statistique Canada, 2013)

Statistics Canada data sources on official-language minorities (n°91-549-X-n°2) - Lafrenière, Sylvie (Statistics Canada, 2013)

Autonomie culturelle, cultures sociétales et vitalité des communautés de langue officielle en situation minoritaire au Canada - Landry, Rodrigue (Minorités linguistiques et société, 2012)
Partant d’un modèle macroscopique des facteurs associés à la vitalité d’une minorité linguistique en situation intergroupe, cet article présente cinq principes expliquant comment les structures sociales s’imposent sur les vécus langagiers des membres de la minorité. Ce même modèle montre comment tant les individus que la collectivité peuvent exercer leur autonomie langagière pour contrer ce déterminisme social. Le modèle de l’autonomie culturelle est explicité et appliqué aux communautés de langue officielle en situation minoritaire (CLOSM) dans le but de faire valoir leur besoin d’autonomie institutionnelle pour assurer leur vitalité au Canada. La reconnaissance du droit à l’autonomie culturelle pourrait être un mode de légitimation des droits propres à ces communautés. Les CLOSM sont décrites comme des prolongements des deux cultures sociétales qui constituent le fondement de la dualité linguistique canadienne. Mots-clés : autonomie culturelle, culture sociétale, vitalité linguistique, droits linguistiques, minorités linguistiques

La santé des populations de langue officielle en situation minoritaire [numéro thématique] - Leis, Anne; Bouchard, Louise (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Cette page éditoriale présente un numéro spécial de la Revue canadienne de santé publique qui comporte 16 articles compilant certains résultats de recherches obtenus par des chercheurs affiliés au RISF, au RRASFO et à l’Institut de recherche de l’Hôpital Montfort (IRHM), ainsi qu'un commentaire exposant les enjeux d'accès aux services de santé linguistiquement concordant au Pays de Galles.
fs-ref-orig: Leis, A. et Bouchard,

English, French and official language minorities in Canada: Census of population, 2016 (n°98-200-X2016011) - Lepage, Jean-François (Statistics Canada, 2017)
fs-ref-orig: Lepage, J.-F. (2017). English, French and official language minorities in Canada: Census of population, 2016 (n°98-200-X2016011). Statistics Canada. fs-code-orig: Lepage-2017b

Le français, l’anglais et les minorités de langue officielle au Canada : recensement de la population, 2016 (n°98-200-X2016011) - Lepage, Jean-François (Statistique Canada, 2017)
fs-ref-orig: Lepage, J.-F. (2017). Le français, l’anglais et les minorités de langue officielle au Canada : recensement de la population, 2016 (n°98-200-X2016011). Statistique Canada. fs-code-orig: Lepage-2017a

Professionnels de la santé et minorités de langue officielle au Canada, 2001 et 2011 (n°89-657-X 2017002) - Lepage, Jean-François; Lavoie, Émilie (Statistique Canada, 2017)

Identité, culture et représentations de la santé et des maladies - Lévesque, Annabel (Cahiers franco-canadiens de l’Ouest, 2015)
La santé et les maladies représentent des concepts subjectifs qui varient en fonction de nombreux facteurs, notamment la culture d’appartenance. Étant donné le contexte multiculturel canadien, il importe de considérer le contact interculturel lorsqu’on s’interroge au sujet des représentations de la santé et des maladies chez les groupes minoritaires puisque ces derniers sont soumis à l’influence d’autres cultures, dont la culture du groupe dominant. Ainsi, le degré d’identification à la culture d’origine et à la culture dominante détermine les représentations auxquelles souscrivent les individus issus d’un groupe minoritaire. Chez ceux qui s’identifient à leur culture d’origine, on note un lien entre leur état de santé et la vitalité culturelle et linguistique de leur communauté. Les efforts visant à promouvoir la santé et le bien-être de ces individus devraient donc être axés sur le maintien de leur héritage culturel et linguistique. Les professionnels de la santé, pour leur part, devraient engager le dialogue avec leurs patients au sujet de leurs représentations culturelles de la santé et des maladies, et ce, dans un climat empreint de respect. Cette pratique pourrait contribuer à la satisfaction des patients avec les soins reçus et, par le fait même, à l’adoption de comportements sains.

Methodological issues in analysing small populations using CCHS cycles based on the official language minority studies - Makvandi, Ewa; Bouchard, Louise; Bergeron, Pierre-Jerôme; Sedigh, Golnaz (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Statistical analyses for small populations or small domains of interest can be challenging. To obtain reliable estimates, only very large surveys such as the Canadian Community Health Survey can be considered. However, despite its good geographical and temporal coverage, the analysis of small populations in smaller regions (e.g., health regions) and in regards to specific health issues remains challenging. We will look at the methodological issues in analysis of small populations in relation to sampling and non-sampling survey errors that affect the precision and accuracy of the estimates. Francophone minorities in Canada will be used to illustrate the issues throughout the paper.

Language barriers: Use of regular medical doctors by Canada's official language minorities - Ngwakongnwi, Emmanuel; Hemmelgarn, R., Brenda; Musto, Richard; King-Shier, Kathryn M.; Quan, Hude (Canadian Family Physician, 2012)

L’offre active de services en français : généalogie d’un outil de politique publique - Normand, Martin (Francophonies d'Amérique, 2019)
L’offre active de services en français est un principe qui s’est rapidement imposé dans le discours des principaux intervenants dans le domaine de la promotion et de la protection des langues officielles et de la dualité linguistique au Canada. Elle a été intégrée à des politiques, à des règlements et à des lois au palier fédéral et dans plusieurs provinces canadiennes. Plusieurs travaux ont été consacrés aux aspects liés à la mise en oeuvre du principe. Cet article va au-delà de ces contributions pour retracer l’histoire de l’offre active. Il répond à deux questions : 1) quelle est l’origine de l’offre active ? et 2) quels sont les principaux jalons dans son évolution et sa diffusion ? L’hypothèse est que les représentations initiales de l’offre active n’étaient pas que techniques ou formalistes et qu’elles se sont effritées avec le temps. La recherche repose essentiellement sur des sources primaires et secondaires, qui nous ont permis de reculer jusqu’au moment où le principe semble avoir émergé. Le texte s’organise autour de trois périodes : la conceptualisation, l’institutionnalisation et la diffusion de l’offre active.

Enjoying your senior years in your own language, culture and community. Federal support from key institutions and a portrait of English-speaking seniors in Quebec - Office of the commissioner of official languages (Federal support from key institutions and a portrait of English-speaking seniors in Quebec, 2013)

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

Official language minority communities in Canada: Is linguistic minority status a determinant of mental health? - Puchala, Chassidy; Leis, Anne; Lim, Hyun; Tempier, Raymond (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
fs-ref-orig: Puchala, C., Leis, A., Lim, H., & Tempier, R. (2013). Official language minority communities in Canada: Is linguistic minority status a determinant of mental health? Canadian Journal of Public Health, 104(1), 5‑11. https://www.ncbi.nlm.nih.gov/pmc/Articles/PMC6973939/pdf/41997_2013_Article_1040605.pdf fs-code-orig: Puchala-2013

Canadian medical schools addressing Francophone minority needs - Schofield, Aurel; Bardeau-Rodigue, Danielle; Leblanc, P. (Social Innovations Journal, 2019)
le lien a été discontinué: https://socialinnovationsjournal.org/editions/issue-56/75-disruptive-innovations/2988-canadian-medical-schools-addressing-francophone-minority-needs

Exploring the determinants of language barriers in health care (LBHC): Toward a research agenda for the language sciences - Segalowitz, Norman; Kehayia, Eva (The Canadian Modern Language Review, 2011)
There is growing interest in language barriers in health care (LBHC) – interest, that is, in how the quality of health care service delivery might be compromised when patients and health care providers do not share the same first language. This article discusses LBHC as an emerging research area that provides valuable opportunities for researchers in various branches of the language sciences – including, among others, applied linguistics, theoretical linguistics, psycholinguistics, second language acquisition – to conduct basic research and to make contributions to the socially important area of medical communication. This article also proposes a research agenda aimed at attracting general language researchers to the study of LBHC, an agenda that is theory driven, programmatic, problem-solving oriented, and interdisciplinary in scope. In proposing this agenda, selected examples have been reviewed from the current literature that can serve as illustrative models for how future research into LBHC can proceed.

Favoriser le rétablissement dans sa langue. Orientation en santé mentale en français. Version révisée - Société Santé en français (Version révisée, 2014)
fs-ref-orig: Société santé en français. (2012). Favoriser le rétablissement dans sa langue. Orientation en santé mentale en français. Version révisée. fs-code-orig: Société Santé en français-2014

Sensibilisation, structuration et consolidation en santé en français : 10 ans d’action - Société Santé en français (Reflets, 2014)

Comparing mental health of Francophone populations in Canada, France, and Belgium: 12-month prevalence rates of common mental disorders (part 1) - Tempier, Raymond; Vasiliadis, Helen-Maria; Gilbert, Fabien; Demyttenaere, Koen; Bruffaerts, Ronny; Bonnewyn, Anke; Lépine, Jean-Pierre; Gasquet, Isabelle; Mosier, Karen; Lesage, Alain; Puchala, Chassidy; Lepnurm, Marje; et al. (The Canadian Journal of Psychiatry, 2010)
Objective: To compare the 12-month prevalence of common mental disorders among francophones in Canada, France, and Belgium. This is the first article in a 2-part series comparing mental disorders and service use prevalence of French-speaking populations. Methods: This is a secondary analysis of data from the Canadian Community Health Survey: Mental Health and Well-Being (CCHS 1.2) in 2002 and the European Study of Epidemiology of Mental Disorders-Mental Health Disability (ESEMeD) from 2001 to 2003, where comparable questionnaires were administered to representative samples of adults in Canada, France, and Belgium. In Canada, francophone respondents living in Quebec (n = 7571) and outside Quebec (n = 500) completed the French version of the CCHS 1.2 questionnaire. Francophone respondents in Belgium (n = 389) and in France (n = 1436) completed the French version of the ESEMeD population survey questionnaire. Major depressive episodes (MDEs), specific anxiety disorders (ADs), and alcohol abuse and (or) dependence disorders' rates were assessed. Results: The overall prevalence rate for the presence of any MDE, AD, or alcohol abuse and (or) dependence was similar in all francophone populations studied in Canada and Europe and averaged 8.5%. Conclusions: Mental disorders were equally distributed in all francophone populations studied. Cross-national comparisons continue to be instrumental in providing information useful for the creation of appropriate policies and programs for specific subsets of populations.

Comparing mental health of Francophones in Canada, France, and Belgium: 12-month and lifetime rates of mental health service use (part 2) - Tempier, Raymond; Vasiliadis, Helen-Maria; Gilbert, Fabien; Demyttenaere, Koen; Bruffaerts, Ronny; Lépine, Jean-Pierre; Gasquet, Isabelle; Lepnurm, Marje; Lesage, Alain; Puchala, Chassidy; Mosier, Karen; Kovess-Masféty, Viviane (The Canadian Journal of Psychiatry, 2010)
Objectives: To compare 12-month and lifetime service use for common mental disorders in 4 francophone subsamples using data from national mental health surveys in Canada, Quebec, France, and Belgium. This is the second article in a 2-part series comparing mental disorders and service use prevalence of French-speaking populations. Methods: Comparable World Mental Health-Composite International Diagnostic Interviews (WMH-CIDI) were administered to representative samples of adults (aged 18 years and older) in Canada during 2002 and in France and Belgium from 2001 to 2003. Two groups of francophone adults in Canada, in Quebec (n = 7571) and outside Quebec (n = 500), and respondents in Belgium (n = 389) and France (n = 1436) completed the French version of the population survey. Prevalence rates of common mental health service use were examined for major depressive episodes and specific anxiety disorders (that is, agoraphobia, social phobia, and panic disorder). Results: Overall, most francophones with mental disorders do not seek treatment. Canadians consulted more mental health professionals than their European counterparts, with the exception of psychiatrists. Conclusions: Patterns of service use are similar among francophone populations. Variations that exist may be accounted for by differences in health care resources, health care systems, and health insurance coverage.

Désinstitutionalisation psychiatrique en Acadie, en Ontario francophone et au Québec, 1930-2013 - Thifault, Marie-Claude; Dorvil, Henri (Presses de l’Université du Québec, 2015)

Regards croisés Ontario-Québec : les services de soins de santé mentale des communautés de langue officielle en situation minoritaire de 1950 à nos jours - Thifault, Marie-Claude; Lebel, Marie; Perreault, Isabelle; Desmeules, Martin (Reflets, 2012)
Considérant qu’un Canadien sur neuf hospitalisé pour maladie mentale retournera à l’urgence moins d’un mois après sa sortie d’hôpital, il importe de documenter, dans une perspective socio-historique, les itinéraires « transinstitutionnels » des personnes souffrant de troubles psychiques. Nous proposons ici une note de recherche sur l’enquête que nous menons sur l’évolution des services de soins de santé mentale des communautés de langue officielle en situation minoritaire, en particulier, les communautés francophones de l’Est et du Nord ontarien ainsi que de la communauté anglophone de l’Ouest du Québec. Ces regards croisés entre deux régions francophones de l’Ontario et le Montréal anglophone visent une meilleure compréhension de l’impact des facteurs de « langue de service » et de « culture » sur la santé mentale des communautés francophones en situation minoritaire (CFSM). Mots-clés : services de santé mentale, désinstitutionnalisation, minorités linguistiques, Ontario, Québec

Pour des services de santé culturellement et linguistiquement adaptés - Tremblay, Suzanne (Société Santé en français et Société Santé et Mieux-être en français du Nouveau-Brunswick, 2011)
Ce document fait rapport des études : Les normes de compétences culturelles et linguistiques en santé : étude exploratoire sur les normes américaines et Étude sur les services de santé linguistiquement et culturellement adaptés : portrait pancanadien.

Enjeux des services sociaux et de santé en contexte bilingue ou multilingue national. Revue de littérature - van Kemenade, Solange; Forest, Mariève (Secrétariat national du Consortium national de formation en santé, 2015)

Bilan de santé : une analyse descriptive de l’état de la recherche sur la santé et les communautés francophones en situation minoritaire - Vézina, Sylvain (Minorités linguistiques et société, 2015)
Ce texte présente un bilan des activités de recherche soutenues par le Consortium national de formation en santé (CNFS), selon l’orientation des connaissances produites et des pistes d’action qui en résultent. Nous y abordons la question de la participation du milieu à la planification de la recherche, sa réalisation et la mise en pratique des résultats. L’étude a été réalisée selon deux méthodes : une analyse du contenu des documents produits et une série d’entrevues avec des chercheurs et des représentants du milieu. L’objectif consiste à fournir quelques indications sur les atouts et les défis du rapprochement entre chercheurs et communautés dans la perspective de la recherche participative. Mots-clés : production en recherche, santé des minorités, minorité francophone du Canada, mise en pratique des connaissances, recherche participative, rapprochement chercheurs-communautés

Vers une démarche concertée pour le renforcement de la recherche sur les langues officielles dans le secteur de la santé : bilan et pistes d’action - Vézina, Sylvain; Doiron Robichaud, Johannie (Bureau d’appui aux communautés de langue officielle de Santé Canada, 2011)
fs-ref-orig: Vézina, S. et Doiron Robichaud, J. (2011). Vers une démarche concertée pour le renforcement de la recherche sur les langues officielles dans le secteur de la santé : bilan et pistes d’action. Bureau d’appui aux communautés de langue officielle de Santé Canada. http://docplayer.fr/123792385-Vers-une-demarche-concertee-pour-le-renforcement-de-la-recherche-sur-les-langues-officielles-dans-le-secteur-de-la-sante-bilan-et-pistes-d-action.html fs-code-orig: Vézina-2011

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the increase in international mobility, healthcare systems should no longer be ignoring language barriers. In addition to the benefit of reducing long‐term costs, immigrant‐friendly organizations should be concerned with mitigating the way language barriers increase individuals’ social vulnerabilities and inequities in health care and health status. This paper reports the findings of a qualitative, exploratory study of the health literacy of 28 Francophone families living in a linguistic‐minority situation in Canada. Analysis of interviews revealed that participants’ social vulnerability, mainly due to their limited social and informational networks, influenced the construction of family health literacy. Disparities in access to healthcare services could be decreased by having health professionals’ work in alliance with Francophone community groups and by hiring bilingual health professionals. Linguistic isolation and lack of knowledge about local cultural organizations among Francophone immigrants were two important findings of this study.